Intraoperative cardiovascular response of natural orifice transluminal endoscopic surgery versus laparoscopy: A comparative animal study - Patrascu, Stefan (J Minim Access Surg, 2018)
BACKGROUND: Natural orifice transluminal endoscopic surgery (NOTES) emerged as a new alternative method in minimally invasive techniques. Although a very small number of studies have compared the physiologic response in NOTES to laparoscopy, the results remain controversial. AIM: This experimental animal study aims to evaluate the intraoperative cardiovascular and respiratory effects of pure transluminal natural orifice surgery and conventional laparoscopy. MATERIALS AND METHODS: Twenty female pigs (Sus scrofa domesticus) equally divided into two study groups were assigned to either pure natural orifice transluminal endoscopic techniques (Group 1) or conventional laparoscopic surgery (Group 2) and monitored intraoperatively in terms of heart rate (HR), systolic blood pressure (SBP) and O(2) saturation (SpO(2)) for 1 h. Both groups underwent simple surgical procedures such as gastrojejunostomy, oophorectomy and adnexectomy. RESULTS: All procedures were successfully completed. The findings indicated statistically significant differences between SBP (P = 0.0065) and SpO(2) (P = 0.027) in the two groups at the beginning of the interventions. HR showed significant differences during the last 20 min of the interventions (min 40 and 45; P < 0.001). For the whole procedure (from the beginning of the intervention to 60 min interval), HR, SBP and SpO(2) values showed no statistical difference. CONCLUSIONS: Although significant differences in terms of HR, mean blood pressure and SpO(2) were noted at specific intervals during surgery, no real variance of the cardiovascular parameters was observed when considering the entire procedure. Therefore, NOTES seems to be a safe approach with minimally intraoperative cardiovascular and respiratory implications.